In vitro effects of Crotalus durissus terrificus and Bothrops jararaca venoms on Giardia duodenalis trophozoites - Shinohara, L.; de Freitas, S. F.; da Silva, R. J.; Guimaraes, S. (Springer, 2006)
Considering the snake venoms' pharmacological properties and chemotherapeutic potential as well as the need for new alternatives for Giardia infection treatment, the present study was carried out aiming to evaluate the in vitro effects of crude Crotalus durissus terrificus and Bothrops jararaca venoms on the growth and adherence of Giardia duodenalis trophozoites. Trophozoites (10(6)) were exposed to serial twofold dilutions of C. durissus terrificus and B. jararaca venoms that ranged from 3.125 to 200 mu g/ml and from 5 to 320 mu g/ml, respectively. The two venoms inhibited the growth of trophozoites, and the level of inhibition varied according to the assayed concentrations and incubation times. The highest reduction of parasite growth was observed with increasing concentrations of the venoms. No effect on parasite adherence was observed. Light microscope observations revealed changes of the pear-shape aspect of the cell and reduction of flagellar beating frequency in the great part of the trophozoites. This is the first attempt to evaluate the in vitro effects of snake venoms on Giardia trophozoites. The findings stress the need for more investigations and prompt us to perform further studies to identify active principles with antigiardial effect.